GENETIC DIVERSITY OF THE CAPTIVE CHINESE POND TURTLE (MAUREMYS REEVESII) P OPULATIONS IN CHINA ASSESSED BY MICROSATELLITE MARKERS - X. Bu; X. Wang; W. Lu; W. Cai; X. Xia; L.Nie (Journal of Animal and Plant Sciences, 2019)
The Chinese pond turtle (Mauremysreevesii) is one of the most important commercial and medicinal chelonians in China. In this study, 87Chinese pond turtle individuals were collected to represent five captive populations of this species in China. Twelve polymorphic microsatellite markers were used to evaluate the genetic diversity of five cultured populations, and it revealed that the level of genetic diversity was relatively high in these cultured populations. Except for Mclw03, Mclw06 and Mmu1 in the GZ population, all microsatellite loci of the other four populations did not deviated from Hardy–Weinberg equilibrium. The analysis of molecular variance (AMOVA) revealed that 80.7% of the genetic variation within populations and 19.3% among populations. Pair wise FST further showed that there was moderate to high degree of genetic differentiation between populations. Phylogenetic analysis separated the Chinese pond turtle samples in the present study into two clusters, with the first group included Guangzhou, Nanning and Haikou populations and the second group consist of individuals from two populations from Wuhu. Our results demonstrated that different degrees of inbreeding existed in five captive populations and it is urgent to raise a new superior breeding population with high genetic diversity using turtles from different captive populations.
Keywords: Chinese pond turtle; Mauremysreevesii; Microsatellite; Genetic diversity; Genetic variation